2021
DOI: 10.14569/ijacsa.2021.0120284
|View full text |Cite
|
Sign up to set email alerts
|

Particle Physics Simulator for Scientific Education using Augmented Reality

Abstract: In this era of fourth industrial revolution, young learners need to be equipped with 21 st century skills, such as critical thinking, creativity, communication, collaboration, innovation and problem solving. Augmented Reality (AR) based learning systems are an effective tool to embed these skills. This paper presents a detailed review of latest research on an AR-based learning systems. Furthermore, an AR-based learning system is proposed to demonstrate the particle physics experiments i.e. proton-proton collis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…AR is a type of technology that superimposes information in the real world, which can be visualized from a technological tool, to interact and enrich various types of information, according to [1] [2], there are different types of AR, including visual augmentation, haptic feedback and multimodal feedback [3]. AR like many digital technologies encompasses algorithms, which, in this case, allow to distort of reality, counting with additional information which is attractive to the user [4] [5], being so, this tool joins the 3 dimensions of the elements created in a digital way, texts, images and real videos, visible in a real-world [6], AR technology nowadays covers different fields, as well as AR applied in education, video games, medicine, architecture, etc., taking into account that many of them have the objective of raising awareness about certain topics and instructing greater knowledge, which is a support for society [7].…”
Section: Introductionmentioning
confidence: 99%
“…AR is a type of technology that superimposes information in the real world, which can be visualized from a technological tool, to interact and enrich various types of information, according to [1] [2], there are different types of AR, including visual augmentation, haptic feedback and multimodal feedback [3]. AR like many digital technologies encompasses algorithms, which, in this case, allow to distort of reality, counting with additional information which is attractive to the user [4] [5], being so, this tool joins the 3 dimensions of the elements created in a digital way, texts, images and real videos, visible in a real-world [6], AR technology nowadays covers different fields, as well as AR applied in education, video games, medicine, architecture, etc., taking into account that many of them have the objective of raising awareness about certain topics and instructing greater knowledge, which is a support for society [7].…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions about students' affective domain of learning in the context of AR have been drawn through interviews, written surveys, observations, and even EEG measurements. It has been found that students who learned with AR were more intensively engaged in classroom discussions [36,39,77,85,117,120,122,131], were more focused [10,54,78,110,117], showed more enjoyment and interest [10,36,43,46,54,62,68,75,83,85,89,105,112,115,117,119,131] and more often overcame prejudices against the course [36]. Additionally, in the study by Arici et al the teacher reported that students liked to learn within an AR environment because it reminded them of a game environment [36].…”
Section: Positive Effects On Affective Domain Of Learningmentioning
confidence: 98%
“…This happens particularly often when some of the representations include many features irrelevant to achieving the learning objectives. For example, this may be the case for the activity that includes playing football with balls that represent protons [62]. In order to be in a position, to more objectively evaluate the effectiveness of learning activities, it would be useful if future ARstudies would more often report the different types of cognitive load induced by certain activities.…”
Section: Stars and Constellations In The Skymentioning
confidence: 99%
“…They tested their proposed model on Zalando datset and they confirmed that they achieved accuracy rate of 81%. In 2021 Hyder et al [23] studied the capabilities of Microsoft Kinect sensor and the role of augmented reality in simulating the surrounding world. The authors confirmed that 85% of the volunteers experienced their system and recommended it as a good 3D learning system.…”
Section: Literature Reviewmentioning
confidence: 99%